Development of a consultation system for regression analysis - Kittipong Asawapichayon; Huynh, Ngoc Phien; Malhotra, Vishv Mohan; Kanchana Kanchanasut; The Australian Government (Bangkok : Asian Institute of Technology, 1988)
The multiple linear regression expert system (MREX) is built although a lot of regression analysis packages are available because existing regression packages require considerable knowledge for their efficient use. For these packages it is the responsibility of the user to decide the regression method and suitable testing to accomplish the analysis of each problem. Besides, the regression analysis is not confined itself only to statisticians but is also used by researchers in many areas where their problems might be unable to be analyzed effectively by statisticians without the specific knowledge in that area. MREX which can be used not only by the statistician , is then developed to reduce these problems. In the consulting session , it uses the facts acquired from the user together with its own statistical testing routines to c heck the data at hand and comes out with the suitable regression method for that set of data. Information and suggestions are given to the user during the processing so that one with little knowledge in statistics can gain more knowledge. For the knowledge base, it is represented by using production rules where the forward chaining is the strategy used by the inference engine.
A thesis submitted in partial fulfillment. of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Regression analysis -- Computer programs